2015
DOI: 10.1016/j.ijnurstu.2014.10.013
|View full text |Cite
|
Sign up to set email alerts
|

The provision of emotional labour by health care assistants caring for dying cancer patients in the community: A qualitative study into the experiences of health care assistants and bereaved family carers

Abstract: Please cite this article as: Lovatt, M., Nanton, V., Roberts, J., Ingleton, C., Noble, B., Pitt, E., Seers, K., Munday, D.,The provision of emotional labour by health care assistants caring for dying cancer patients in the community: a qualitative study into the experiences of health care assistants and bereaved carers, International Journal of Nursing Studies (2014Studies ( ), http://dx.doi.org/10.1016Studies ( /j.ijnurstu.2014 This is a PDF file of an unedited manuscript that has been accepted for publicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 30 publications
4
32
0
Order By: Relevance
“…Conferring a value on psychosocial aspects of care, and demonstrating it in multidisciplinary practice situations, can support and encourage flexibility in other professionals. This aspect was exemplified through the enhanced role of HCAs in Macmillan Specialist Care at Home and may reflect findings from other research [70] which suggests that their input is significant in community palliative care to complement existing provision.…”
Section: Discussionmentioning
confidence: 69%
“…Conferring a value on psychosocial aspects of care, and demonstrating it in multidisciplinary practice situations, can support and encourage flexibility in other professionals. This aspect was exemplified through the enhanced role of HCAs in Macmillan Specialist Care at Home and may reflect findings from other research [70] which suggests that their input is significant in community palliative care to complement existing provision.…”
Section: Discussionmentioning
confidence: 69%
“…Literature findings for this workforce have been published in relation to educational interventions (Ingleton et al, 2011, Murray, 2012, Pesut et al, 2015, Weir, 2015, and Kyle et al, 2015; job satisfaction, (Holmberg et al, 2013, andVan der Linde, 2014); role development, patient safety and quality of care , Lovatt et al, 2015, and Swedberg et al, 2013). …”
Section: Evolution Of Hswsmentioning
confidence: 99%
“…Additionally, care workers not only clinically contribute to holistic care but also contribute to psychological care in the community setting. Lovatt et al (2015) identified that HSWs provide emotional support for patients in end stage life. This is an enhanced key aspect of their role.…”
Section: Role Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The grown connections between patients and the PCA are what feeds the PCA's passion. According to Lovatt et al [3] PCAs possess the sentiment that one of their essential roles is delivering emotional support for patients. A fire can be seen behind the eyes of PCAs when they begin to speak about the method in which they ensure high-quality care.…”
Section: The Passion Of the Pcamentioning
confidence: 99%